Dimensional Reduction and Localization of a Bose-Einstein Condensate in a Quasi-1D Bichromatic Optical Lattice - Salasnich, L.; Adhikari, K. [UNESP] (Polish Acad Sciences Inst Physics, 2015)
We analyze the localization of a Bose-Einstein condensate in a one-dimensional bichromatic quasi-periodic optical-lattice potential by numerically solving the 1D Gross-Pitaevskii equation (1D GPE). We first derive the 1D Gross-Pitaevskii equation from the dimensional reduction of the 3D quantum field theory of interacting bosons obtaining two coupled differential equations (for axial wave fuction and space-time dependent transverse width) which reduce to the 1D Gross-Pitaevskii equation under strict conditions. Then, by using the 1D Gross-Pitaevskii equation we report the suppression of localization in the interacting Bose-Einstein condensate when the repulsive scattering length between bosonic atoms is sufficiently large.